Investigating America's most notorious strip club: the FBI, the Gold Club, and the Mafia - Sewell, Mark (Rowman & Littlefield, 2024)
"Get the inside scoop on the nation's most sensational mafia trial of the early 2000s. From Jay Leno to the Washington Post and from Sports Illustrated to CNN, the Gold Club trial received more media coverage than the 1999 trial of Gambino Family Boss, John Gotti, Jr"--